Cationic antimicrobial peptides do not change recombination frequency in Escherichia coli. (31st March 2018) - Rodríguez-Rojas, Alexandro; Moreno-Morales, Javier; Mason, A. James; Rolff, Jens
Abstract : Cationic antimicrobial peptides are ubiquitous immune effectors of multicellular organisms. We previously reported, that in contrast to most of the classic antibiotics, cationic antimicrobial peptides (AMPs) do not increase mutation rates in E. coli . Here, we provide new evidence showing that AMPs do not stimulate or enhance bacterial DNA recombination in the surviving fractions. Recombination accelerates evolution of antibiotic resistance. Our findings have implications for our understanding of host–microbe interactions, the evolution of innate immune defences, and shed new light on the dynamic of antimicrobial-resistance evolution.